Procedural complications of inferior vena cava filter retrieval, an illustrated review - Quencer, Keith B. (CVIR Endovasc, 2020)
Annually, approximately 65,000 inferior vena cava (IVC) filters are placed in the United States (Ahmed et al., J Am Coll Radiol 15:1553–1557, 2018). Approximately 35% of filters are eventually retrieved (Angel et al., J Vasc Interv Radiol 22: 1522–1530 e1523, 2011). Complications during filter retrieval depend heavily on technique and filter position. In this paper, we review risk factors and incidence of complications during IVC filter removal. We also discuss ways these complications could be avoided and the appropriate management if they occur.